ENGLISH KNOWLEDGE IN THE TRAVEL AGENTS IN MANTA. - GÓMEZ P., ARMANDO B. (2015)
MANTA, AS ONE OF THE MOST IMPORTANT SEAPORT, HAS AN IMPORTANT AND VARIED HOTEL INFRASTRUCTURE, 23 TRAVEL AGENCIES INCLUDING THE 5 WHOLESALERS (IATA), AN INTERNATIONAL AIRPORT WITH EXTENSIVE LIST OF FLIGHTS OPERATED, AND A DEEP-WATER PORT. THE OLDEST TRAVEL AGENCY IN ECUADOR IS METROPOLITAN TOURING.